Membangun Generasi Muda Dusun Ngandong yang Tangguh: Menangkal Bahaya Napza dan Kenakalan Remaja melalui Penguatan Karakter - Al Fajri, Ahmad Rifki; Rahmayanti, Aprilia; Fathurrahman, Lalu Adrian; Fadillah, Mohammad Iqbal; Fikri, Muhammad Rizalul; Nuha, Muhammad Ulin; Marwati, Pury Yan; Ratnasari, Ratnasari; Rahayu, Sekar Amalia; Almayda, Verga Nyctagina; Susilawati, Desi (Universitas Muhammadiyah Yogyakarta, 2025)
Community Service is a form of student service to the community to increase social awareness and welfare. Through this program, students are expected to play an active role in helping the community overcome various social problems. Some of the main issues that are currently of concern include drug abuse, weak character development, and increased juvenile delinquency, which have a negative impact on the younger generation, both in terms of health, morals, and the future. Lack of understanding about the dangers of drugs, character building and juvenile delinquency are the main factors in the emergence of deviant behavior. The Community service program implemented in Ngandong Hamlet educates children, teenagers and young people about the dangers of drug abuse, the importance of character building, and the negative impact of juvenile delinquency. This program was motivated by the increasing risk of using addictive substances and the low awareness of the younger generation in building good character. The methods used were socialization, counseling, and interactive discussions. The socialization aimed to provide an understanding of the negative impact of drugs and the importance of positive character, while the interactive discussion provided an opportunity for participants to share their experiences and ask questions, as well as discuss their daily challenges. The results of this activity showed an increase in participants' understanding of the dangers of drugs as well as awareness of the importance of building a strong character and the installation of educational banners in three strategic locations to expand the dissemination of information and increase public awareness. The output of this activity was 25 participants, more than 60% of whom stated that they gained new insights and were better prepared to deal with negative influences in their environment. The program not only provides education but also instills values such as honesty, discipline and courage